2013
DOI: 10.1080/15226514.2013.773283
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacteria in the Rhizosphere Soils ofPolygonum Pubescensand Their Potential in Promoting Growth and Cd, Pb, Zn Uptake byBrassica napus

Abstract: Microbe-enhanced phytoremediation has been considered as a promising measure for the remediation of metal-contaminated soils. In this study, two bacterial strains JYX7 and JYX10 were isolated from rhizosphere soils of Polygonum pubescens grown in metal-polluted soil and identified as of Enterobacter sp. and Klebsiella sp. based on 16S rDNA sequences, respectively. JYX7 and JYX10 showed high Cd, Pb and Zn tolerance and increased water-soluble Cd, Pb and Zn concentrations in culture solution and metal-added soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In many cases, the effects of plant–microbe interactions on growth and metal uptake has been shown to be species- and soil-specific ( Sheng et al, 2008 ; Becerra-Castro et al, 2012 ; Cabello-Conejo et al, 2014 ), but interesting results have also been obtained by inoculating Ni-resistant PGPR isolated from the rhizosphere of Alyssum serpyllifolium and Astragalus incanus on the growth and Ni accumulation of Ricinus communis , Heliantus annus , and Brassica juncea , grown in single and multiple metal-contaminated soils ( Ma et al, 2011a , b , 2015a ; Jing et al, 2014 ). Cd- and Pb-mobilizing rhizospheric bacteria also enhanced the uptake of metals in tomato plants ( Jiang et al, 2008 ) and Zn-mobilizing bacteria, isolated from serpentine soils, promoted Zn, Cu, and Ni accumulation in R. communis ( Rajkumar and Freitas, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the effects of plant–microbe interactions on growth and metal uptake has been shown to be species- and soil-specific ( Sheng et al, 2008 ; Becerra-Castro et al, 2012 ; Cabello-Conejo et al, 2014 ), but interesting results have also been obtained by inoculating Ni-resistant PGPR isolated from the rhizosphere of Alyssum serpyllifolium and Astragalus incanus on the growth and Ni accumulation of Ricinus communis , Heliantus annus , and Brassica juncea , grown in single and multiple metal-contaminated soils ( Ma et al, 2011a , b , 2015a ; Jing et al, 2014 ). Cd- and Pb-mobilizing rhizospheric bacteria also enhanced the uptake of metals in tomato plants ( Jiang et al, 2008 ) and Zn-mobilizing bacteria, isolated from serpentine soils, promoted Zn, Cu, and Ni accumulation in R. communis ( Rajkumar and Freitas, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, metal accumulating plants are not necessarily tolerant and may be subject to metal toxicity at high metal concentrations, leading to poor remediation efficiency (Ebbs and Kochian 1997). Inoculating hyperaccumulators with plant growth promoting bacteria (PGPB) has been demonstrated to promote growth in contaminated environments (de- Bashan, Hernandez, and Bashan 2012;Jing et al 2014), potentially offering a sustainable remediation technology for toxic metal contaminants. However, the effects of PGPB on plant growth promotion under high soil metal contamination are not always satisfactory and remediation efficiency is still relatively low (Zhuang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…CC30 significantly enhanced Cu uptake by sunflowers. Moreover, Jing et al (2014) reported that Enterobacter sp. JYX7 and Klebsiella sp.…”
Section: Resultsmentioning
confidence: 99%